Bifurcation and Chaos in Fractional-Order Systems - Danca, Marius-F; Chen, Guanrong (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This book presents a collection of seven technical papers on fractional-order complex systems, especially chaotic systems with hidden attractors and symmetries, in the research front of the field, which will be beneficial for scientific researchers, graduate students, and technical professionals to study and apply. It is also suitable for teaching lectures and for seminars to use as a reference on related topics.